SISTEM INFORMASI GEOGRAFIS LETAK SEKOLAH MENENGAH PERTAMA (SMP) SATU ATAP BERBASIS ANDROID DI WILAYAH KABUPATEN GORONTALO - Farid, Farid; Jabbar, Asnia (Journal Of Software Engineering And Communication, 2024)
Problems in this system is the District Education Office Gorontalo is only limited information available geographically manual picture on a sheet of paper which is used as a document to see where the location of the school This eliminates. The aim of this study is to help the user or community Gorontalo or migrant communities in the search for locations via visual maps . Gorontalo community in using the map can help to get some information about an object map by entering the name of the object sought in this regard on the This eliminates specialize in Gorontalo Regency. Results of the testing system flowchart and white box to add the data flowgraph pharmacies as well as the junior SATAP is N = 7 , E = 7. As for the blackbox testing each presses the button on the mapping application SATAP android SMP is in line with the results expected by the user application